2021
DOI: 10.3389/froh.2021.649406
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Interleukin-1ß and Interleukin-8 in Oral Potentially Malignant Disorders and Carcinomas

Abstract: Objective: To evaluate interleukin-1ß (IL-1ß) and interleukin-8 (IL-8) epithelial expressions in potentially malignant disorders of the oral mucosa as malignant predictive markers.Study design: About 55 tissues embedded in paraffin, comprising 15 oral lichen planus (OLP) lesions, 15 leukoplakias, 15 oral squamous cell carcinomas (OSCC), and 10 samples of normal oral mucosa were included in the study. IL-1ß and 8 expressions were assessed by immunohistochemistry using antibodies antihuman IL-1ß human (sc-7884, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…To elucidate the mechanism by which OSCC cells regulate p‐ACLY level and lipid synthesis in fibroblasts, we searched for exocrine molecules of OSCC cells that can function as AKT agonists. Interleukin‐8 (IL8) was identified in previously published reports as a possible upstream regulator 31–35 . We examined IL8 expression in The Cancer Genome Atlas database using the GEPIA website.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To elucidate the mechanism by which OSCC cells regulate p‐ACLY level and lipid synthesis in fibroblasts, we searched for exocrine molecules of OSCC cells that can function as AKT agonists. Interleukin‐8 (IL8) was identified in previously published reports as a possible upstream regulator 31–35 . We examined IL8 expression in The Cancer Genome Atlas database using the GEPIA website.…”
Section: Resultsmentioning
confidence: 99%
“…Interleukin‐8 (IL8) was identified in previously published reports as a possible upstream regulator. 31 , 32 , 33 , 34 , 35 We examined IL8 expression in The Cancer Genome Atlas database using the GEPIA website. Results indicated that IL8 was upregulated in head and neck squamous cell carcinoma tissues (Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…To elucidate the mechanism by which OSCC cells regulate p-ACLY level and lipid synthesis in broblasts, we reviewed the literature and searched for exocrine molecules that are highly expressed in OSCC cells and can function as AKT agonists. As a result, IL8 was identi ed in the literature as a possible upstream regulator [29][30][31][32]. Then we examined IL8 expression in the TCGA database using the Gene Expression Pro ling Analysis (GEPIA) website.…”
Section: Resultsmentioning
confidence: 99%
“…It has now been shown that IL8 is not only an in ammatory chemokine, but also a pro-cancer factor. Substantial elevation of IL8 expression was detected in various types of cancer including OSCC, and IL8 has been reported to stimulate angiogenesis, recruit immunosuppressive cells, promote epithelial-to-mesenchymal transition, and enhance stemness and chemoresistance of tumor cells [30,[36][37][38][39]. Notably, activation of AKT signaling is one of the major mechanisms by which IL8 regulates the phenotype and function of tumor and stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Galectin-3 may be upregulated in COVID-19 cohorts (A1,2,3) but the amount found in saliva were near saturation for the GCFP assay as configured. Finally, IL-8 cytokines are produced by a wide range of cells including oral keratinocytes and are a potential biomarker for predicting oral disease (Finoti et al, 2017;Lopez-Labady et al, 2021). IL-8 was also reported early in the pandemic to be a sensitive serum biomarker in both mild and severe COVID-19 patients .…”
Section: Discussionmentioning
confidence: 98%